2020
DOI: 10.1088/1755-1315/548/4/042008
|View full text |Cite
|
Sign up to set email alerts
|

Studying the metabolism of horses when feeding them zeolite-sapropel feed additives in the conditions of Yakutia

Abstract: The article presents the results of study on the effect of zeolite-sapropel feed additives on the metabolism of mares in Central Yakutia. Three groups of horses were formed to conduct scientific experiments. These groups were selected based on the principle of analogues, which took into account age, body weight and fatness. The control group got a basic ration. The experimental groups got a zeolite-sapropel feed additives to the basic ration in doses of 0.5 g of zeolite per kg of body weight with 200 and 300 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The co-use of zeolites and sapropels in animal feeding is of profound research interest. Scientific studies carried out on a group of lactating mares of Megezhek breed in the conditions of Central Yakutia have showed that the organomineral zeolite-sapropel fodder additive has a positive effect on the animals' metabolism and milk productivity [26].…”
Section: Introductionmentioning
confidence: 99%
“…The co-use of zeolites and sapropels in animal feeding is of profound research interest. Scientific studies carried out on a group of lactating mares of Megezhek breed in the conditions of Central Yakutia have showed that the organomineral zeolite-sapropel fodder additive has a positive effect on the animals' metabolism and milk productivity [26].…”
Section: Introductionmentioning
confidence: 99%